Scenario of the Treatment of Arthritis with Natural Products - Gallotti, Fernanda C.M.; Serafini, Mairim R.; Thomazzi, Sara M. (Recent Patents on Inflammation & Allergy Drug Discovery, 2020)
Background: Conventional treatments of arthritis use toxic and poorly tolerated drugs. Therefore, natural products are an alternative because they are important sources of bioactive substances with therapeutic potential. Objective: To perform synthesis of patent applications associated with the use of natural products in the technological development of the invention for use in treating arthritis. Methods: The search for patents was conducted using the following databases of World Intellectual Property Organization (WIPO), European Patent Office (EPO, Espacenet), United States Patents and Trademark Office (USPTO) and National Institute of Intellectual Property (INPI) using as keywords - arthritis, treatment and the International Patent Classification (IPC) A61K36 / 00. Results: A total of 617 patents related to the subject were registered in the period available in patents databases during the study period from the years 2005 to 2017, of which 44 were analyzed based on the established inclusion criteria. The most important countries for protecting these inventions were China, followed by the United States of America, the Republic of Korea and Japan. As for the typology of depositors, that were identified by Educational Institutions and Public Institutes of Research (IEIPP) and Companies and Private Research Institutes (EIPP). Conclusion: The analysis of patents made it possible to characterize the natural products used in the treatment of arthritis, with emphasis on botanical extracts (71%), as a single component, as well as in association with other botanical extracts, isolated compounds and minerals.
Keywords: anti-inflammatory